Anti-arthritic potential of crude sulfated polysaccharide from marine macroalgae Sargassum ilicifolium (Turner) C. Agardh: Regulation of cytokine cascade - Ramamoorthi Lavanya; Jeyabalan Srikanth; Sankar Seethalakshmi; Begum M. Yasmin; Duraipandian Chamundeeswari; Sekar Mahendran; Wong Ling Shing; Subramaniyan Vetriselvan (Biomolecular Concepts)
Seaweeds have been utilized as food, fodder, fertilizer, and medicine since ancient times; nevertheless, they have received only a little attention. In the current work, we extracted the sulfated polysaccharide from a marine source and investigated its anti-arthritic potential in vivo. The isolated and freeze-dried polysaccharide was tested for acute oral toxicity based on OECD 423. This step was followed by investigations on clinical signs and gross pathological alterations seen. A complete Freund’s adjuvant-induced arthritis was used to test the in vivo activity in female Sprague–Dawley rats, which were divided into five groups: (1) normal control, (2) arthritic control, (3) methotrexate treatment (0.1 mg/kg), (4) crude sulfated polysaccharide (CSP) (5 mg/kg), and (5) CSP (10 mg/kg). CSP was from the marine brown algae Sargassum ilicifolium from the Gulf of Mannar. The body weight, paw volume, and biochemical markers (alanine aminotransferase, aspartate aminotransferase, creatinine, urea, and C-reactive protein levels) were also measured for each group coupled with histopathological and immunohistochemistry studies. The acute toxicity investigation indicated that the lethal dose of 50% (LD50) of the polysaccharide was more than 2,000 mg/kg. In addition, animals from the methotrexate and CSP (5 mg/kg, p.o.) groups had a substantial reduction in paw volume compared to other treatment groups. Methotrexate and CSP treatment dramatically decreased the levels of the investigated marker enzymes. Histopathology revealed that low-dose CSP (5 mg/kg, p.o.) significantly reduced the severity of synovitis, panniculitis, liver necrosis, inflammatory cell infiltration, and cortical and paracortical necrotic foci in node, compared to the high dose (10 mg/kg, p.o.). Immunohistochemical studies revealed that CSP (5 mg/kg) significantly inhibited pro-inflammatory cytokines such as tumor necrosis factor-alpha, interleukin-2, and CD4 cells. Overall, it can be concluded that a low-dose CSP (5 mg/kg) is an efficient anti-arthritic agent that confers its effects via the cytokine pathway.